ESTRATEGIAS DE ENSEÑANZA-APRENDIZAJE Y SU IMPACTO EN EL RENDIMIENTO ACADÉMICO DE LOS ESTUDIANTES EGB. - LOPEZ ROJAS ISRAEL JEFTE QUINTO (2024)
The document addresses the impact of teaching-learning strategies on the academic performance of fifth-year EGB students at the Luis Letamendi school. It is highlighted that low academic performance can be influenced by the lack of effective pedagogical strategies, the importance of addressing this problem is emphasized to support the equitable development and well-being of students through the implementation of effective teaching-learning strategies. Specific objectives are proposed, such as identifying the positive impact of these strategies on academic performance, analyzing the relationship between their use and results, and evaluating performance through quantitative indicators. The proposed hypothesis maintains that the implementation of these strategies will have a significant impact on academic performance. The results obtained through tests applied to students show the need to implement specific strategies to improve areas such as the acquisition of knowledge and the development of autonomous thinking. In conclusion, the study seeks to promote improvements in academic performance through effective teaching-learning strategies that promote meaningful learning and contribute to the well-being and comprehensive development of students.